Study on the guidelines for the efficient and sustainable management of groundwater usage revenue collection in relation to groundwater usage fees and groundwater preservation fees in the groundwater crisis areas of Thailand - Vijitsri Sanguanwongse; Mana Luksamee-Arunothai; Supanee Harnphattananusorn; Kanokon Seemanon; Wasin Siwasarit; Setthabut Ittithumwinit (Environmental and Sustainability Indicators, 2024)
This study attempts to examine the cost and benefits of shifting the collection process of groundwater revenue and groundwater preservation fees from a manual to automatic meter reading (AMR) system, utilizing marginal cost and marginal benefit. The methodology is based on a benefit-cost analysis, taking into account the monetary value of time. The following specific results are revealed: (1) Changing to an AMR system can provide additional benefits in terms of time-savings for current personnel since the administrative work relating to the collection of groundwater usage fees and groundwater preservation fees can be reduced by 70%. This study is based on two personnel per province, calculated using the rate of 26,397.46 baht (or 792.95 USD) per person per month, 70% of which equates to an opportunity cost of 18,000 baht (or 540.70 USD) per person per month. (2) The accident rate can be reduced if personnel do not need to travel to examine the groundwater usage of licensees. However, because the AMR system is complicated and customizable, transitioning from manual to AMR systems is not a one-size-fits-all proposition. We propose that a pilot project be carried out to properly implement the AMR installation process.